Masculinity in Metropop Novel - Nisfatul Syarifa; Azizatuz Zahro (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2022)
Masculinity refers to the ideal nature of male constructed by society. Developments in various sectors make masculinity grows, which one is metrosexual male. Metrosexual are men who are identified as men whoare very concerned with appearances that emerge as the impact of popular culture and hedonism lifestyle on modern urban society. In this study, the masculinity of metrosexual characters in the metropop novels is examined. Masculinity in metropop novels shows masculinity with an urban life setting that puts forward aspect of appearance like an attractive face, fashion that relies on fashion trends and particular brands, and economic financial stability.